Ropa - Easterling, Lisa. (Chicago, Ill. : Heinemann Library, 2007)
Describes the different types of clothes throughout the world and what the clothing is made of.
"Bellota"--Cover.
Includes index.
Keywords: Clothing and dress -- Juvenile literature; Prendas de vestir -- Literatura juvenil